Pemanfaatan Multi Media dalam Pembelajaran dan Pembinaan Kerohanian Siswa di SMTK Willfinger Krayan - Jerry Doni; Daniel Nubatonis (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
This research examines the use of multimedia in the spiritual development of students at SMTK Willfinger Krayan. The main objective of the study was to evaluate the effectiveness of using various digital media in improving the understanding and appreciation of spiritual values among students. The methods used included direct observation, interviews with teachers and students, and content analysis of multimedia used in the spiritual formation program. The results showed that the use of multimedia, such as inspirational videos, digital bible applications, and interactive presentations, significantly increased students' interest and participation in spiritual activities. In addition, it was found that the multimedia approach helped students more easily understand and apply spiritual teachings in their daily lives. This study concludes that the integration of multimedia in spiritual formation is an effective strategy to improve the quality of spiritual education at Willfinger Krayan SMTK.